Application of the Willis Covered Stent in the Treatment of Complex Vascular Diseases of the Internal Carotid Artery and Vertebral Artery: A Retrospective Single-Center Experience - Wu YG; Wang B; Cui H; Zhu H; Gao G (Dove Medical Press, 2023)
Yin-Gang Wu,1,* Bowen Wang,2,* Hao Cui,3,* Hao Zhu,1 Ge Gao1- 3 1Department of Neurosurgery, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, Anhui, 230001, People's Republic of China; 2Department of Neurosurgery, Wannan Medical College, Wuhu, Anhui, 241001, People's Republic of China; 3Department of Neurosurgery, Bengbu Medical College, Bengbu, Anhui, 233030, People's Republic of China*These authors contributed equally to this workCorrespondence: Ge Gao, Department of Neurosurgery, The First Affiliated Hospital of University of Science and Technology of China, Hefei, Anhui, People's Republic of China, Email gegao1012@163.comObjective: To retrospectively evaluate the efficacy and security of Willis covered stent (WCS) deployment for complex vascular diseases of the internal carotid (ICA) and vertebral (VA) arteries.Methods: Retrospective analysis was performed on complex vascular disease patients (n=36) treated with WCSs at our center between March 2017 and December 2022, with a 3- 36-months follow-up surveillance and digital subtraction angiography (DSA) examination.Results: The WCSs were successfully deployed in all the patients. The 36 included lesions were carotid-cavernous sinus fistulas (CCFs; n=10) (27.8%), complex saccular aneurysms (n=10) (27.8%), traumatic pseudoaneurysms (n=7) (19.4%), blood blister-like aneurysms (BBAs; n=5) (13.9%), and iatrogenic carotid or vertebral artery ruptures (n=4) (11.1%). The WCS was released at the communicating segment (n=2) (5.6%), the ophthalmic segment (n=3) (8.3%), the clinoid and cavernous segment (n=28) (77.8%), the petrous segment (n=2) (5.6%) of ICA and the V3 segment (n=1) (2.8%) of VA. Postoperative DSA showed complete lesion occlusion in 26 patients (72.2%) who were immediately treated with WCSs, and endoleaks occurred in 3 patients (8.3%) (endoleaks resolved postadjustment in 7 patients (19.4%)). In patients (n=3) (8.3%) treated with double stents at the break of the ICA, the endoleak remained in 1 CCF patient (2.8%) during the 3-month follow-up, and the residual shunt disappeared after the second stent system was placed 3 months later. No aneurysm, bleeding or infarct recurrence reported, and only 1 patient (2.8%) had mild asymptomatic in-stent stenosis. Deaths and procedural complications did not occur during follow-up.Conclusion: Treatment with a WCS for intracranial complex vascular diseases resulted in satisfactory clinical outcomes and appeared effective and safe. Controlled, multicenter, large sample sizes and longer follow-up periods studies are necessary.Keywords: Willis covered stents, complex vascular diseases, endovascular treatment